Addressing Water Pollution Crimes in Poland and Lithuania: Legal and Judicial Perspectives - Solodov, Denis; Zębek, Elżbieta; Žilinskienė, Leda (PRAWO i WIĘŹ, 2026)
The United Nations’ 2030 Agenda for Sustainable Development underscores the critical need to address water pollution, emphasising the importance of effective measures for its mitigation and prevention. In alignment with these global priorities, the European Union’s Directive 2008/99/EC on the protection of the environment through criminal law established key principles for holding individuals and legal entities responsible for environmental harm, including water pollution. The Directive mandated the implementation of proportionate and dissuasive criminal penalties to deter environmentally harmful behaviour. Reflecting these standards, Polish and Lithuanian criminal law treat water pollution as a serious offence, recognizing its potential to cause significant environmental degradation. The new Directive 2024/1203 of the European Parliament and of the Council on the protection of the environment through criminal law, which has replaced Directive 2008/99/EC, strengthens the framework for imposing effective, proportionate, and dissuasive criminal penalties. Its provisions aim to ensure that the penalties correspond to the gravity of the offences. The authors analyse the provisions of the new Directive and examine ongoing concerns related to judicial leniency in handling environmental offences in cases concerning natural persons. They argue that, in light of both the UN’s Agenda 2030 and evolving EU legislation, proportionate and consistent criminal penalties are essential to effectively combat environmental crimes, including water pollution.